Nghiên cứu mô hình mô tả phân tử các chất có hoạt tính ức chế Enzym Kinesin Spindle Protein Eg5 / Thái Khắc Minh, Trần Thành Đạo, Lê Minh Trí - Thái, Khắc Minh
With regard that human mitotic kinesin Eg5 functions helping the formation of bipolar mitotic spindle and has been identified as a potential target for new drug development in cancer chemotherapy, and 2D-QSAR model helpful for prediction of Eg5-inhibitory in silico activity was developed as a basis for research into cancer drug development. A total of 92 dihydropyrazoles, dihydropyrroles, 4-phenyltetrahydro isoquinolines and thiophenes derivatives were collected from five scientific reports. 2D-QSAR model were performed using the PLS analysis on a training set of 74 compounds and a test set of 18 compounds. The 2D-QSAR was built with 5 molecular descriptors of 92 compounds, so successful with R2 = 0.86; RMSE = 0.47; = 0.81; = 0.09. By this model, virtual screening revealed 296 compounds from Drug Bank Database and 2464 compounds from ChemDiv library having potential inhibitory activity on Eg5. The obtained model was reliable and the virtual screening results may orientate the design of new cancer drug.